EFFECT OF IV DEXAMETHASONE ON INCIDENCE OF NAUSEA AND VOMITING AND BEGINNING OF ORAL INTAKE IN ADENOTONSILLECTOMY - A A. Etemadi Aleagha, (Babol University of Medical Sciences, 2006)
BACKGROUND & OBJECTIVE: Tonsillectomy and adenotonsillectomy are two of the most common surgical procedures performed in children. Although new surgical technique has reduced immediate postoperative hemorrhage, other complications such as postoperative nausea and vomiting (PONV), pain, poor oral intake, dehydration and fever, however, continues to be a concern in children undergoing tonsillectomy. The purpose of the present study was to determine whether one single, large dose of IV dexamethasone administered before surgery could decrease PONV and improve oral intake after surgery.METHODS: This study was performed on 50 children, 2-12 yr of age undergoing adenotonsillectomy. To specifically delineate the contribution of dexamethasone, all anesthetic and nonanesthetic factors that could influence the incidence of PONV were standardized. Each child received dexamethasone 1 mg/kg (maximal dose 25 mg) (steroid group) or an equal volume of saline (control group) before initiation of surgery.FINDINGS: Twenty seven children were in steroid group and 23 children were in control group. There were no significant differences between two groups with respect to age, weigh and sex but the incidence of PONV was lower in steroid group in both in the recovery (0.00 vs. 0.30 ± 0.5 in control group) ( p= 0.007) and in the ward (0.22 ± 0.6 vs. 0.82 ± 0.9 in control group) (p= 0.010). Oral intake begins after 1.64 ± 0.74 hr vs. 1.96 ± 1.1 in control group. CONCLUSION: Compared with placebo, dexamethasone significantly decreased the incidence of PONV in the immediate and late post operative period (6 hr and 6-24 hr, respectively) but it didn influence oral intake.